IDENTIFIKASI KEMAMPUAN SOFT SKILLINTRAPERSONAL DAN INTERPERSONAL MAHASISWA YANG MENGIMPLEMENTASIKAN KURIKULUM BERBASIS KOMPETENSI (KBK) - Muhammad " Abrar; Ari Pristiana Dewi; Sofiana " Nurchayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract A nurse is inseparable from a quality and standardized health service process. Its existence requires nurses to be able to have competence in providing nursing care. Changing global progress and competitiveness demands Higher Education (University) to produce graduates who are competent, able to meet work ethics, communication skills and have emotional intelligence. The competency standard is contained in the curriculum of college learning system in the form of Competency Based Curriculum (CBC). CBC has a purpose to graduate from university have the ability in the aspects of cognitive, affective and psychomotor so that soft skill become an important indicator to be developed on the lecturing. The purpose of this research is to identify soft skill for student of School of Nursing Riau University (SN UR). This research was conducted at University of Riau, nursing campus during May - June 2017 by using simple descriptive method. Sample selection method used in this study is proportional random sampling with a total sample of 175 respondents. Data collection is done by using questionnaires and data processing is done by computerization process which is displayed in the form of frequency distribution and percentage. The results showed that the soft skill form of students School of Nursing Riau University with the highest score in the good category was Tactfull (76.6%). Soft skill with the lowest score in the good category owned by School of Nursing Riau University is Communication ability (26,9%). It is suggested to students of School of Nursing Riau University to maintain and improve soft skill so that later nursing graduates can provide comprehensive and holistic nursing care to clients. Keywords: soft skill, Curriculum Based Competence (CBC), students